Measurement of cytotoxicity and irritancy potential of sugar-based surfactants on skin-related 3D models. (April 2017) - Lu, Biao; Miao, Yong; Vigneron, Pascale; Chagnault, Vincent; Grand, Eric; Wadouachi, Anne; Postel, Denis; Pezron, Isabelle; Egles, Christophe; Vayssade, Muriel
Abstract: Sugar-based surfactants present surface-active properties and relatively low cytotoxicity. They are often considered as safe alternatives to currently used surfactants in cosmetic industries. In this study, four sugar-based surfactants, each with an eight carbon alkyl chain bound to a glucose or a maltose headgroup through an amide linkage, were synthesized and compared to two standard surfactants. The cytotoxic and irritant effects of surfactants were evaluated using two biologically relevant models: 3D dermal model (mouse fibroblasts embedded in collagen gel) and reconstituted human epidermis (RHE, multi-layered human keratinocytes). Results show that three synthesized surfactants possess lower cytotoxicity compared to standard surfactants as demonstrated in the 3D dermal model. Moreover, the IC50s of surfactants against the 3D dermal model are higher than IC50s obtained with the 2D dermal model (monolayer mouse fibroblasts). Both synthesized and standard surfactants show no irritant effects after 48 h of topical application on RHE. Throughout the study, we demonstrate the difficulty to link the physico-chemical properties of surfactants and their cytotoxicity in complex models. More importantly, our data suggest that, prior to in vivo tests, a complete understanding of surfactant cytotoxicity or irritancy potential requires a combination of cellular and tissue models. Highlights: Synthesized sugar-based surfactants were tested on multi-scale biological models. The choice of biological models modulates the surfactant cytotoxicity. A methodology for skin-related surfactant safety evaluation is proposed.